Clinical and epidemiological profile of cervical cancer in Piaui in the period from 2017 to 2021 - Amaro, Zuleide Andrade; Monteiro, Larissa Cecy Lustosa do Rego; de Carvalho, Argus Constâncio; Sousa, Virgínia Moreira; Pinto, Bruna Wendy Capistrano; costa, Isabel karoline de sousa carvalho (Seven Editora, 2023)
Cancer is the main public health problem in the world. The prevalence and incidence have been increasing over the years due to factors such as aging, changes in lifestyle (sedentary lifestyle, industrialized foods), and also due to greater contact with some risk factors brought about by urbanization. The Department of Informatics of the Unified Health System (DATASUS) exposes the data so that researchers can monitor and analyze actions for cancer control, in addition to guidelines for research related to the topic (BRAY et al., 2014). DOI: https://doi.org/10.56238/devopinterscie-080